2018
DOI: 10.14419/ijet.v7i3.2.14420
|View full text |Cite
|
Sign up to set email alerts
|

Construction Industry in Ukraine Credit Analysis

Abstract: Construction is one of the national economy key areas since its operating results are of prime importance for the economic and social development of the country. It is due to the fact that this branch is characterized by a long-term manufacturing cycle and significant materials requirements. Construction enhancement in Ukraine is the principal precondition for successful national development, as far as all the interrelated sectors grow proportionally. Present day construction market conditions and construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Revealing the essence of the export potential is necessary to identify the motives that induce the region's economic system and business entities to export their resources and products to develop and promote a strategy for the country's increasing participation in the international division of labour (Onyshchenko et al, 2018;Sopilko, 2013). The study of the problem showed that such a strategy has several advantages over import substitution.…”
Section: Methodologically-analytical Basismentioning
confidence: 99%
“…Revealing the essence of the export potential is necessary to identify the motives that induce the region's economic system and business entities to export their resources and products to develop and promote a strategy for the country's increasing participation in the international division of labour (Onyshchenko et al, 2018;Sopilko, 2013). The study of the problem showed that such a strategy has several advantages over import substitution.…”
Section: Methodologically-analytical Basismentioning
confidence: 99%